John Woodhouse: Gabriele D'Annunzio: defiant archangel - Fairservice, David (Spunti e Ricerche, 2016)
The "influence" of Joyce on Gadda was marginal. Gadda felt belittled rather than flattered by being repeatedly compared with Joyce. If there is a certain "family resemblance" between the two writers, this is due to the forebears whom they shared: Dante, Rabelais, Shakespeare and D'Annunzio.